Identifying sex-specific differences in the carotid revascularisation literature: findings from a scoping review. Issue 3 (29th March 2021) - Yogendrakumar, Vignan; Shamy, Michel; Dewar, Brian; Fergusson, Dean A; Dowlatshahi, Dar; Hamel, Candyce; Gocan, Sophia; Fedyk, Mark; Mas, Jean-Louis; Rothwell, Peter; Howard, Virginia; Bereznyakova, Olena
Abstract : Objective: No systematic review of the literature has dedicated itself to looking at the management of symptomatic carotid stenosis in female patients. In this scoping review, we aimed to identify all randomised controlled trials (RCTs) that reported sex-specific outcomes for patients who underwent carotid revascularisation, and determine whether sufficient information is reported within these studies to assess short-term and long-term outcomes in female patients. Design, setting and participants: We systematically searched Medline, Embase, Pubmed and Cochrane libraries for RCTs published between 1991 and 2020 that included female patients and compared either endarterectomy with stenting, or any revascularisation (endarterectomy or stenting) with medical therapy in patients with symptomatic high-grade (>50%) carotid stenosis. Results: From 1537 references examined, 27 eligible studies were identified. Sex-specific outcomes were reported in 13 studies. Baseline patient characteristics of enrolled female patients were reported in 2 of those 13 studies. Common outcomes reported included stroke and death, however, there was significant heterogeneity in the reporting of both periprocedural and long-term outcomes. Sex-specific differences relating to the degree of stenosis and time from index event to treatment are largely limited to studies comparing endarterectomy to medical therapy. Adverse events were not reported by sex. Conclusions: Only half of the previously published RCTs and systematic reviews report sex-specific outcomes. Detailed analyses on the results of carotid artery intervention for female patients with symptomatic stenosis are limited.